Pathophysiological concepts of the syndrome of chronic fatigue and clinical features as a basis for building physical rehabilitation programs - Bogdanovska, Nadezhda; Kalonova, Iryna; Pozmogova, Natalia (Journal of Education, Health and Sport, 2016)
The syndrome of chronic fatigue is an extremely urgent and complex problem of modern medicine due to the widespread prevalence in the population, with a clear tendency to a steady increase in the incidence. Purpose: to determine the pathophysiological concepts of the syndrome of chronic fatigue. Methods of research: analysis of scientific literature, synthesis and generalization. Results. The syndrome of chronic fatigue is a disease with a complex pathogenesis involving deep disorders of the regulation of the central nervous system and immune system, disorders of cellular energy metabolism, ion transport and cardiovascular disorders. Infectious-inflammatory, psychoneurological and vegetative-endocrine complexes of sympoms are characteristic for this disease. Unlike other diseases of civilization, no specific causative agent has been identified and no clear connection has been established with genetic, hereditary, environmental factors. There are only theories of the pathogenesis of the syndrome of chronic fatigue and a number of factors that increase the possibility of its occurrence. The most popular are infectious (viral), immune and endocrine theories. Conclusions: Complex pathophysiological features of the syndrome of chronic fatigue cause the need for an integrated system approach to diagnosis, treatment and prevention of this disease, including physical rehabilitation.